IMPLEMENTASI MANAJEMEN KURIKULUM PESANTREN DALAM MEMBENTUK KARAKTER MANDIRI SANTRI DI PONDOK PESANTREN NURUS SIBYAN AMBAT TLANAKAN PAMEKASAN - Tamlihah Tamlihah; Abd. Mukhid; Hilmi Qosim Mubah (re-JIEM (Research Journal of Islamic Education Management), 2020)
Independent character is something that must be formed and developed in educating. This research is about the implementation of pesantren curriculum management in forming the independent character of santri in the Nurus Shibyan Ambat Tlanakan Pamekasan Islamic Boarding School by using a qualitative approach with descriptive types through interviews, observation and documentation. The results of the study show that: First the management of the pesantren curriculum in shaping the character of the santris' independence is using planning, organizing and evaluating. Secondly, the formation of the independence character in the Nurus Shibyan Islamic boarding school is more for coaching, namely through fostering exemplary, fostering advice or encouragement. Third, supporting factors in forming the independence of santries are team cohesiveness, teacher involvement in forming the character of independence, and santri motivation in training or activities. The inhibiting factors are minimal facilities and infrastructure of Islamic boarding schools, financing factors, and the behavior of santries who are sometimes undisciplined.